DFT Study and ADMET Investigation of Bioactive 2-Phenoxyquinolines - Oluwafemi S. Aina; Mujeeb O. Rofiu; Luqman A. Adams; Oluwole B. Familoni (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Pharmacologically active quinoline compounds show interesting functionalities. However, there is still a dearth of information on the potential wide applications of the quinoline scaffolds especially when the substituents on the rings or functionalities are modified. In this study 2-phenoxyquinoline-3-carbaldehyde derivatives were synthesized and investigated using DFT to determine the molecular parameters, electronic and chemical reactivity descriptors including their possible application as drug candidates. Geometry optimisations were carried out using Becke three-parameter hybrid functional combined with Lee-Yang-Parr correlation functionals and augmented basis set with added sets of diffuse s- and p-functions: BL3YP /6-311++G(d,p). Drug-likeness scores and bioactivity prediction were carried out using the webserver programs ADMET Sar 2. Our results showed slightly lower energy values in water than in ethanol depicting high reactiveness of the 2-phenoxyquinolines in water especially compounds with fluoro- and methoxy substituted having the lowest Egap of 3.79 eV and 3.381 eV respectively. The methoxy substitution confers higher susceptibility to electron transfer and chemical reactive in aqeous medium. The ionization potential energies were lower in water and ethanol when compared to the other gas states calculated values. The MEP surfaces of all the compounds investigated reveals the ether oxygen atoms and carbonyl groups as necessities for effective antioxidant properties. It is noteworthy that five of the compounds investigated have high activity values above 3.0 octanol–water partition coefficient value indicating an excellent inhibitory activity and strong chemical reactivity. Good oral bioavailability was shown by the compounds depicting their excellent activity as kinase inhibitors, nuclear receptor compounds and enzyme inhibitors. It is noteworthy that cytochromes CYP2C19, CYP2C29, CYP2D6 and CYP3A4 are not inhibited and therefore do not pose potential adverse drug reactions or toxicity. Interestingly, only one compound showed one violation. Consequently, such scaffolds are potential drug candidates.